WISATA KE MASA LALU: POTENSI HERITAGE TOURISM PADA RUMAH IBADAH KUNO DI TANJUNGPINANG - Syahrul Rahmat (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2022)
Tanjungpinang, one of the cities in Kepulauan Riau province in Indonesia, has been inherited with potential cultural heritage buildings. These buildings are witnesses of events from hundreds of years ago. One type of the heritage building is houses of worship such as mosques, churches and temples. The ancient house of worship is still normally visited by its believers and also becomes an alternative tourism attraction. This study aims to deal with the historicity of houses of worship and cope with the potentiality of cultural heritage becoming a heritage tourism destination. Rooting in a case study approach, this research explicates the potentiality of cultural heritage in Tanjungpinang as a heritage tourism destination. Further, a historical research method was employed to delve into the historicity of ancient houses of worship. The results indicate that the ancient house of worship in Tanjungpinang is potentially developed to be one of the heritage tourism destinations. The development of this tourism attraction is an effort of preserving cultural heritage buildings and the values therein